COST ACCOUNTING IN JAPAN: HISTORICAL EVOLUTION, CONTEMPORARY PRACTICES AND BEHAVIOURAL DIMENSIONS - ALecturer, Majid Ahmed AL Anssari; BLecturer, Hind Shafeeq Nimr (Scholars Digest Publishing, 2025)
The current research aims to shed light on cost accounting in Japan. It begins by providing a historical introduction to cost accounting in Japan, including the most important standards issued since the 1930s, the reasons for their change, and their role in the Japanese national economy. This is tailed by a description of the Japanese cost accounting system, its most important functions and objectives, and the role cost accounting has played in practical human resources education in Japan, such as universities and academic institutions. Furthermore, a space is devoted to presenting cost accounting techniques, Japanese society's preferences for the most important of these techniques, and the reasons behind these preferences. The research also highlights the behavioural aspects practiced by Japanese companies and how to motivate workers to decrease costs rather focusing on the control of cost. It also examines the key features of cost accounting management as a collaborative method and a common language between the firm, its clienteles, and dealers.
Keywords: Japanese cost accounting systems, job costing system, sales costing system, objectives and functions of Japanese cost accounting, standard costing method.